Preparation of Cr2O3/Al2O3 bipolar oxides as hydrogen permeation barriers by selective oxide removal on SS and atomic layer deposition. (3rd May 2019) - Zhang, Mengyuan; Zhao, Rongyi; Ling, Yunhan; Wang, Rongguang; Zhou, Qingyun; Wang, Jipeng; Li, Yunhui; Zhang, Zhengjun
Abstract: Iron-nickel based stainless steel (SS) applied in nuclear plants as a substrate material barely suppresses the permeation of hydrogen plasmas, which are mainly composed of positive and negative hydrogen ions with trace amounts of non-ionized hydrogen atoms. In this work, a new Cr2 O3 /Al2 O3 bipolar oxide barrier was prepared using atomic layer deposition (ALD) of Al2 O3 on a Cr2 O3 layer that was generated by removing partial oxides with cyclic voltammetry (CV) of SS that had been pre-oxidized at 550 °C in air. We found that a small layer of α-Al2 O3 was formed by the template effect of Cr2 O3 at the interface of this composite film. The hydrogen permeation behavior of this bipolar oxide barrier in a fusion reactor was simulated with hydrogen-discharging plasma treatment. The results demonstrated that the hydrogen permeation resistance of this bipolar oxide was superior to the original oxide or a Cr2 O3 film. Impressively, hydrogen plasma treatment repaired the bipolar oxide via reduction of the defective CrO3, resulting in an improvement in the hydrogen permeation resistance. These findings demonstrate a novel method of hydrogen permeation barrier preparation on SS, providing insight into hydrogen barrier construction for future nuclear energy applications. Graphical abstract: Image 1 Highlights: A new Cr2 O3 /Al2 O3 coating is prepared by selective removal of oxides and ALD. α-Al2 O3 is formed at the interface by the template effect of Cr2 O3 . The bipolar oxide exhibits excellent hydrogen permeation resistance.